Ab initio NMR studies of chemical constituents of piper sarmentosum - Ibrahim Ali , Noorbatcha (Universiti Malaya, 2002)
The structures of two compounds,gamma-asarone (1-ally1-2,4,5-trimethoxybenzene) {1} and asarylaldehyde (2,4,5-trimethoxybenzaldehyde) {2) from Piper sarmentosum, locally known as 'kaduk', have been studied by HNMR, CNMR spectroscopy and quantum chemical calculations. The NMR shifts are calculated using Hartree Fock (HF) and Density Functional Theory (DFT) methods. We find that the ab initio calculations are very useful in assigning the NMR peaks and provide insights on the electronic factors affecting the NMR shifts.